Aspectos das interações comunicacionais midiatizadas: o caso SENAC–Faculdades - Beretta, Cláudia Maria (Universidade do Vale do Rio do Sinos, 2010)
This paper intends to present a case study within the scope of the educational institution named Senac, in an attempt to understand aspects of its communicational production. The case is configured upon the entrance of Senac into the context of Higher Education while previously it operated only with Technical Courses. During such transition, stresses exacerbated due to the unavoidable organizational change. And, it is exactly this new circumstance that creates the investigative impulse – knowing that this fact is marked out as something new in relation to the prior conjuncture. The reflection develops within the widest scope of the society changes in a mediatization, in which the organizations reshape the paradigm of the institutional image construction. The research focuses challenges faced by the communicational management of the organizations within this society. The case is studied using interviews and documentary research, on which an analytical-interpretative work is developed. From the records of the
Keywords: midiatização; organizações; interações sociais; mediatization; organizations; social interactions; Ciências Sociais Aplicadas